The global information society - Currie, Wendy (Chichester : John Wiley and Sons, 2000)
The emerging global information society (GIS). Internet commerce. Defining a legal and regulatory framework for Internet commerce. Market as opportunity. Gaining competitive advantage from business-to-consumer internet commerce...
Keywords: Computer; Information technology; Information technology; Information society; Technology -- Social aspects